A pilot study of ultrasound-guided electronic brachytherapy for skin cancer - Goyal, Uma; Kim, Yongbok; Tiwari, Hina Arif; Witte, Russell; Stea, Baldassarre (Journal of Contemporary Brachytherapy, 2015)
Purpose : Electronic brachytherapy (eBT) has gained acceptance over the past 5 years for the treatment of non-melanomatous skin cancer (NMSC). Although the prescription depth and radial margins can be chosen using clinical judgment based on visual and biopsy-derived information, we sought a more objective modality of measurement for eBT planning by using ultrasound (US) to measure superficial (< 5 mm depth) lesions. Material and methods : From December 2013 to April 2015, 19 patients with 23 pathologically proven NMSCs underwent a clinical examination and US evaluation of the lesions prior to initiating a course of eBT. Twenty lesions were basal cell carcinoma and 3 lesions were squamous cell carcinoma. The most common location was the nose (10 lesions). A 14 or 18 MHz US unit was used by an experienced radiologist to determine depth and lateral extension of lesions. The US-measured depth was then used to define prescription depth for eBT planning without an added margin. A margin of 7 mm was added radially to the US lateral extent measurements, and an appropriate cone applicator size was chosen to cover the target volume. Results : The mean depth of the lesions was 2.1 mm with a range of 1-3.4 mm, and the mean largest diameter of the lesions was 8 mm with a range of 2.6-20 mm. Dose ranged from 32-50 Gy in 8-20 fractions with a median dose of 40 Gy in 10 fractions. All patients had a complete response and no failures have occurred with a median follow-up of 12 months (range of 6-22 months). Also, no prolonged skin toxicities have occurred. Conclusions : A routinely available radiological US unit can objectively determine depth and lateral extension of NMSC lesions for more accurate eBT treatment planning, and should be considered in future eBT treatment guidelines.